Perinatal death: Is there a place for post-mortem angio-CT?. Issue 1 (March 2015) - Sarda-Quarello, Laure; Tuchtan, Lucile; Torrents, Julia; Piercecchi-Marti, Marie-Dominique; Bartoli, Christophe; Laurent, Pierre-Eloi; Bourlière-Najean, Brigitte; Petit, Philippe; Quarello, Edwin; Gorincour, Guillaume
Abstract Purpose To study the feasibility of perinatal post-mortem computed tomography angiography (PMCTA) and to evaluate the informations provided. Material and methods From January to March 2014, we included all fetuses referred to our fetopathology unit for intra-uterine fetal death or termination (IUFD) or pregnancy (TOP). We noted sex, gestational age in weeks׳ gestation (WG) at referral, and reason for TOP. All bodies were scanned with the same CT device using the same protocol, before and after contrast injection. We analyzed the success rate of the injection, the quality of vascular filling and the informations provided compared to prenatal data and confirmed by standard autopsy for all patients. Results We prospectively included 17 consecutive attempts of PMCTA in fetuses aged 16–37 WG (mean 28), 9 were male and 8 were female, originating from intra-uterine fetal death (n=4, 23.5%) or termination of pregnancy (n=13, 76.5%). Injection failed in 4 cases (23%). In the 13 successful others (77%), injection was quoted sub-optimal in 2 cases (15%). Overall, additional informations were provided by PMCTA in 5 cases (29%), meaning 38% of cases when injection was successful. Conclusion Perinatal PMCTA is feasible and provides additional data compared to prenatal imaging. We strongly believe it is a very promising technique, especially in association with ultrasound, more or less dedicated brain MRI.